The Relations between Internet using as a Learning Media and the Interest in Learning of Guidance and Counseling Study Program Students - Nur Wisma; Faradillah Rahayu Metrin (IICET (Indonesian Institute for Counseling, Education and Therapy), 2022)
This quantitative descriptive research is an correlational, aiming to determine the relationship between the use of the internet as a learning medium and the learning interest of the 2018 students of the Guidance and Counseling study program at Sriwijaya University. The population in this study were 70 students and a sample of 64 students using proportional random sampling technique. The data collection instrument used a questionnaire using a Likert scale. The data analysis used was the product moment correlation. The results of the analysis obtained a correlation coefficient of 0.574 which indicates that the use of the internet as a learning medium with student interest in learning has a relationship with a rather low level of relationship at a significance level of 0.05. So it can be concluded that there is a relationship between the use of the internet as a learning medium and the interest in learning of students from the 2018 batch of the guidance and counseling study program FKIP Sriwijaya University.